Nitrogen and fluorine co-doped three-dimensional carbon material as well as preparation method and application thereof

By modifying the negative electrode current collector of a negative electrodeless sodium-ion battery with nitrogen-fluorine co-doped three-dimensional carbon materials, the problems of low energy density and safety hazards of traditional sodium-ion batteries are solved, achieving efficient sodium-ion deposition and cycle stability, simplifying the preparation process and reducing costs.

CN121470463APending Publication Date: 2026-02-06湖州超钠新能源科技有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311175163.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Traditional sodium-ion batteries have low energy density, and the negative electrode undergoes large volume changes during cycling, which poses risks of sodium dendrite growth and safety hazards. Furthermore, existing carbon material doping and modification processes are complex and costly.

Method used

A three-dimensional carbon material with high sodium affinity and porous structure was prepared by heating a mixture containing an organic carbon source, a fluorine source and a nitrogen source under a protective atmosphere using nitrogen and fluorine co-doped three-dimensional carbon material. This material can be used as a negative electrode current collector in sodium batteries without negative electrode active material.

Benefits of technology

It improves the uniform deposition of sodium ions, inhibits sodium dendrite growth and negative electrode volume expansion, enhances the cycle stability and coulombic efficiency of the battery, reduces polarization, and has a simple preparation process and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121470463A_ABST
    Figure CN121470463A_ABST
Patent Text Reader

Abstract

The invention provides a nitrogen and fluorine co-doped three-dimensional carbon material as well as a preparation method and application thereof. The preparation method comprises the following steps: in a protective atmosphere, heating a uniform mixture containing an organic carbon source, a fluorine source and a nitrogen source at 400-1000 DEG C to obtain the nitrogen-fluorine co-doped three-dimensional carbon material. When the nitrogen and fluorine co-doped three-dimensional carbon material is used for preparing a sodium ion battery without a negative electrode active layer, the sodium ion deposition process can be well homogenized, sodium dendrite growth and negative electrode volume expansion are inhibited, and the sodium ion battery has relatively low polarization and longer cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new energy technology, specifically relating to a nitrogen-fluorine co-doped three-dimensional carbon material and its preparation method and application, a slurry composition, and a sodium-ion battery without negative electrode active material. Background Technology

[0002] Exploring and developing new and renewable clean energy sources has become a top priority in solving energy and environmental problems. Among numerous new energy technologies, sodium-ion batteries are playing an increasingly important role in the national economy and daily life due to their advantages such as abundant resources, cleanliness, high energy density, and low cost. However, with the development of society and technology, people have increasingly higher requirements for battery energy density. The relatively low energy density of traditional sodium-ion batteries limits their application scenarios.

[0003] Sodium-ion batteries without a negative electrode active material, using only a current collector as the negative electrode, have attracted significant attention from researchers due to the absence of an active material layer, resulting in a substantial increase in cell energy density. However, during cycling, the large volume change of the negative electrode and the growth of sodium dendrites lead to low coulombic efficiency and poor cycle stability, even posing safety hazards such as short circuits. Constructing novel structured negative electrode current collectors using nanotechnology to regulate sodium ion deposition / stripping behavior and mitigate electrode volume changes during cycling is one effective strategy for improving the overall performance of negative electrode-free batteries.

[0004] Carbon possesses advantages such as light weight, good electrical conductivity, good chemical stability, and excellent mechanical properties, making it one of the most widely used materials for modifying anode current collectors in electrodeless batteries. Carbon nanotubes, graphene, carbon fibers, and biomass carbon are all widely used as carrier materials for sodium ion deposition. According to existing reports, they have all improved the performance of sodium metal anodes to some extent. However, directly using the three-dimensional framework constructed from these materials as a carrier for sodium ion deposition often results in high overpotentials and large polarization. Therefore, based on the three-dimensional framework, improving the sodium affinity of the framework material and reducing the sodium nucleation barrier is an effective means to further improve the anode current collector in electrodeless batteries. However, this strategy also has obvious drawbacks. For example, it increases the difficulty of material preparation. On the other hand, materials such as carbon nanotubes and graphene themselves have high requirements for preparation conditions and complex preparation processes. On top of this, doping modification is required, leading to high preparation costs.

[0005] Therefore, developing a negative electrode for sodium batteries without negative electrode active materials that can balance high performance and simple preparation process is of great significance for promoting the practical application of negative electrode-free sodium secondary batteries. Summary of the Invention

[0006] To solve all or part of the above-mentioned technical problems, the present invention provides the following technical solutions:

[0007] One objective of this invention is to provide a method for preparing nitrogen-fluorine co-doped three-dimensional carbon materials. The method includes heating a homogeneous mixture containing an organic carbon source, a fluorine source, and a nitrogen source at 400–1000°C under a protective atmosphere to obtain the nitrogen-fluorine co-doped three-dimensional carbon material. If the heating temperature is too low, the organic carbon source will not carbonize sufficiently or the nitrogen / fluorine source will not decompose sufficiently, thus affecting the performance of the nitrogen-fluorine co-doped three-dimensional material. If the heating temperature is too high, energy consumption will increase significantly.

[0008] In some embodiments, the organic carbon source includes sucrose and / or glucose. Sucrose and glucose are low-cost and suitable as raw materials for industrial production.

[0009] In some embodiments, the nitrogen source includes at least one selected from ammonium fluoride, melamine, ammonia, and nitrogen. The nitrogen source is readily available and economical.

[0010] In some embodiments, the fluorine source includes at least one selected from ammonium fluoride, polyvinylidene fluoride, and carbon tetrafluoride. The fluorine source is readily available and economical.

[0011] In some embodiments, the mass ratio of the organic carbon source, nitrogen source, and fluorine source is 1:(0.1-2):(0.1-2). Within this mass ratio range, it is beneficial to obtain three-dimensional carbon materials with suitable nitrogen and fluorine doping amounts. If the nitrogen source mass is relatively low, the nitrogen doping amount in the prepared three-dimensional carbon material will be low, resulting in insignificant performance improvement. If the nitrogen source mass is relatively high, the nitrogen doping amount in the prepared three-dimensional carbon material will be too high, leading to unstable framework structure and poor conductivity, and increased manufacturing costs. Similarly, if the fluorine source mass is relatively low, the fluorine and nitrogen doping amount in the prepared three-dimensional carbon material will be low, resulting in insignificant performance improvement. If the fluorine source mass is relatively high, the nitrogen doping amount in the prepared three-dimensional carbon material will be too high, leading to unstable framework structure and poor conductivity, and increased manufacturing costs.

[0012] In some embodiments, the heating time is 1 hour to 6 hours. If the heating time is less than 1 hour, the doping is insufficient; if the heating time is more than 6 hours, energy consumption is high and manufacturing costs increase.

[0013] In some embodiments, the homogeneous mixture comprises sucrose and ammonium fluoride in a mass ratio of 1:2 to 10:1. The advantages of this technical solution are that ammonium fluoride can serve as both a nitrogen and fluorine source, and its decomposition products are simple, easy to treat, and entirely gaseous, resulting in good pore-forming properties.

[0014] A second objective of this invention is to provide a nitrogen-fluorine co-doped three-dimensional carbon material obtained according to the preparation method described in any of the above technical solutions. It should be noted that the nitrogen-fluorine co-doped three-dimensional carbon material provided by this invention is hard carbon, possessing a high sodium storage capacity, thus solving the problem of low sodium storage capacity in existing carbon materials such as carbon nanotubes and carbon fibers. Therefore, the nitrogen-fluorine co-doped three-dimensional carbon material provided by this invention can provide additional capacity. After adsorbing and embedding sodium ions, its sodium affinity is improved, further promoting the uniform deposition of sodium on the framework.

[0015] In some embodiments, the nitrogen doping amount in the nitrogen-fluorine co-doped three-dimensional carbon material is 0.01% to 1%, and the fluorine doping amount is 0.01% to 1%.

[0016] In some embodiments, the specific surface area of ​​the nitrogen-fluorine co-doped three-dimensional carbon material is 80 m². 2 / g~500m 2 / g. Nitrogen-fluorine co-doped three-dimensional carbon materials exhibit the best performance within this specific surface area range, with specific surface areas below 80m². 2 / g, the effect of uniform sodium deposition will be weakened, and the specific surface area is higher than 500m². 2 / g, too many active sites, increase side reactions.

[0017] In some embodiments, the porosity of the nitrogen-fluorine co-doped three-dimensional carbon material is 25% to 75%. When the nitrogen-fluorine co-doped three-dimensional carbon material is used to prepare the negative electrode sheet of a secondary battery without a negative electrode active material, its porous structure allows the electrode to have sufficient internal space to accommodate the volume changes of sodium ions during deposition / stripping, thus suppressing problems such as pulverization and side reactions, thereby improving the cycle stability of sodium-ion batteries.

[0018] A third objective of this invention is to provide a slurry composition comprising the nitrogen-fluorine co-doped three-dimensional carbon material described in any of the above-mentioned technical solutions.

[0019] In some embodiments, the slurry composition further includes a dispersant, a conductive agent, and a binder.

[0020] In some embodiments, the dispersant comprises water and / or N-methylpyrrolidone. N-methylpyrrolidone is preferred.

[0021] In some embodiments, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, and graphene.

[0022] In some embodiments, the adhesive includes at least one of CMC (carboxymethyl cellulose), SBR (styrene-butadiene rubber), polyacrylic acid, and PVDF (polyvinylidene fluoride).

[0023] In some embodiments, the content of the nitrogen-fluorine co-doped three-dimensional carbon material in the slurry composition is 30% to 70%.

[0024] A fourth objective of this invention is to provide the application of the nitrogen-fluorine co-doped three-dimensional carbon material or the slurry composition described in any of the above-mentioned technical solutions in the preparation of a negative electrode for a secondary battery or a secondary battery. Preferably, the secondary battery is a sodium-ion battery.

[0025] The fifth objective of this invention is to provide a negative electrode for sodium-ion batteries, comprising the nitrogen-fluorine co-doped three-dimensional carbon material described in any of the above technical solutions.

[0026] The sixth objective of this invention is to provide a sodium-ion battery without negative electrode active material. The sodium-ion battery without negative electrode active material includes a positive electrode, a negative electrode, and an electrolyte. The negative electrode includes a negative electrode current collector and a carbon material layer disposed on the negative electrode current collector. The carbon material layer includes a nitrogen-fluorine co-doped three-dimensional carbon material as described in the above technical solution.

[0027] In some embodiments, the thickness of the carbon material layer is 2–50 μm. If the thickness is less than 2 μm, the performance of the nitrogen-fluorine co-doped three-dimensional carbon material cannot be fully utilized; if it is greater than 50 μm, the three-dimensional carbon material cannot be fully utilized, reducing the energy density of the battery cell.

[0028] In some embodiments, the method of depositing the carbon material layer on the negative electrode current collector includes, for example, coating the surface of the negative electrode current collector with a slurry composition containing carbon material, and then performing a drying process. The drying process includes, for example, baking at a temperature of 120°C for 12 hours.

[0029] Compared with the prior art, the present invention has at least the following beneficial effects:

[0030] (1) The nitrogen-fluorine co-doped three-dimensional carbon material prepared in this invention is rich in sodium-loving functional groups such as pyridine nitrogen, pyrrole nitrogen, and CF bonds. On the one hand, these sodium-loving functional groups provide more uniform nucleation sites and smaller nucleation overpotentials on the surface of the three-dimensional carbon material. On the other hand, the interaction between these polar functional groups and sodium ions can regulate the sodium ion flux in the electrolyte and achieve uniform sodium ion distribution. Therefore, the anode sheet without anode active material prepared by this invention has a more uniform sodium deposition process, and the growth of sodium dendrites and the volume expansion of the anode are suppressed. The sodium secondary battery composed of this material has lower polarization and longer cycle life, solving the problems of low coulombic efficiency, poor cycle stability, and safety hazards caused by large volume changes of the anode and sodium dendrite growth in the prior art.

[0031] (2) In addition, nitrogen and fluorine co-doping showed a good synergistic effect and better electrochemical performance compared with nitrogen doping and fluorine doping alone. This is because nitrogen and fluorine doping can shorten the band gap of carbon, greatly improve the conductivity of carbon skeleton, enhance the adsorption of sodium ions by skeleton, and reduce the diffusion energy of sodium ions in skeleton, thereby reducing polarization and uniform sodium deposition. Nitrogen doping or fluorine doping alone does not have this effect.

[0032] (3) The nitrogen-fluorine co-doped three-dimensional carbon material prepared by the present invention has a large specific surface area and a porous structure. On the one hand, these structural features can greatly reduce the current density on the electrode and guide the uniform deposition of sodium metal. On the other hand, the porous structure can also enable the electrode to have sufficient internal space to accommodate the volume change of sodium ions during the deposition / stripping process, thus suppressing problems such as pulverization and side reactions.

[0033] (4) The carbon material prepared by the present invention is hard carbon, which has a high sodium storage capacity, thus solving the problem that the sodium storage capacity of carbon materials such as carbon nanotubes and carbon fibers in the prior art is low. Therefore, the carbon material prepared by the present invention can provide additional capacity. After adsorbing and embedding sodium ions, the sodium affinity of hard carbon is improved, which further promotes the uniform deposition of sodium on the framework.

[0034] (5) The present invention uses a one-step method to obtain the required nitrogen-fluorine co-doped three-dimensional carbon material. Its preparation process is simple and the raw material cost is low, and it has the potential for large-scale production. Attached Figure Description

[0035] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0036] Figure 1 These are the cycle capacity retention curves of the sodium-ion batteries without negative electrode active material prepared in Example 1, Comparative Example 1, and Comparative Example 2 of this invention.

[0037] Figure 2 This is an XRD pattern of a nitrogen-fluorine co-doped three-dimensional carbon material prepared in one embodiment of the present invention. Detailed Implementation

[0038] The technical solutions of the present invention will be described in detail below with reference to specific embodiments, so that those skilled in the art can better understand and implement the technical solutions of the present invention. The specific functional details disclosed herein should not be construed as limiting, but are merely intended to form the basis of the claims and to teach those skilled in the art to employ the representative basis of the invention in different ways in any suitable detailed embodiment.

[0039] Example 1

[0040] This embodiment provides a sodium-ion battery negative electrode sheet without negative electrode active material and a sodium-ion battery, the preparation steps of which include:

[0041] Sucrose and ammonium fluoride were mixed in a 1:1 mass ratio to form a homogeneous mixture. This homogeneous mixture was then placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min under an argon atmosphere. The temperature was maintained at this temperature for 2 hours to obtain a nitrogen-fluorine co-doped three-dimensional carbon material. Figure 2 This is the XRD pattern of the three-dimensional carbon material prepared in this embodiment. Figure 2 It can be seen that the nitrogen-fluorine co-doped three-dimensional carbon material prepared by this invention is hard carbon;

[0042] After cooling the nitrogen-fluorine co-doped three-dimensional carbon material to room temperature, it was ground in a mortar for 30 minutes. Then it was mixed with polyvinylidene fluoride and conductive carbon black in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone was added to make the slurry solid content 35% to 75%. The mixture was stirred at room temperature for 6 hours to obtain the slurry composition.

[0043] The above slurry composition was coated onto the surface of aluminum foil using a coating machine, and then baked in an oven at 120°C for 12 hours to remove the solvent from the electrode, resulting in a nitrogen-fluorine co-doped three-dimensional carbon material layer with a thickness of 15 μm formed on the aluminum foil.

[0044] Preparation of sodium secondary batteries without negative electrode active materials: The aluminum foil loaded with nitrogen and fluorine co-doped three-dimensional carbon material layer was used as the negative electrode, NaNiFeMn was used as the positive electrode, and the electrolyte was a mixed solution of NaPF6 and EC / PC / EMC, wherein the concentration of NaPF6 in the mixed solvent of EC / PC / EMC was 1 mol / L; the volume ratio of EC / PC / EMC was 1∶3∶6. Sodium-ion batteries were assembled, and electrochemical tests were performed on the assembled sodium-ion batteries. The test results are shown in Table 1.

[0045] Example 2

[0046] The only difference between Example 2 and Example 1 is that sucrose and ammonium fluoride were mixed in a mass ratio of 5:1 to form a homogeneous mixture. The rest of the process was the same as in Example 1. A nitrogen-fluorine co-doped three-dimensional carbon material was prepared and assembled into a sodium-ion battery using the same method as in Example 1. Electrochemical tests were then performed, and the test results are shown in Table 1.

[0047] Example 3

[0048] The only difference between Example 3 and Example 1 is that sucrose and ammonium fluoride were mixed in a mass ratio of 1:2 to form a homogeneous mixture. The rest of the preparation of nitrogen-fluorine co-doped three-dimensional carbon materials was the same as in Example 1. Sodium-ion batteries were assembled and electrochemical tests were performed in the same way as in Example 1. The test results are shown in Table 1.

[0049] Example 4

[0050] The only difference between Example 4 and Example 1 is that sucrose and ammonium fluoride were mixed in a mass ratio of 10:1 to form a homogeneous mixture. The rest of the preparation of nitrogen-fluorine co-doped three-dimensional carbon material was the same as in Example 1. The nitrogen-fluorine co-doped three-dimensional carbon material was prepared and assembled into a sodium-ion battery using the same method as in Example 1. Electrochemical tests were performed and the test results are shown in Table 1.

[0051] Example 5

[0052] The only difference between Example 5 and Example 1 is that the thickness of the nitrogen-fluorine co-doped three-dimensional carbon material layer formed on the aluminum foil is 2 μm. The rest is the same as in Example 1. The sodium-ion battery was assembled and electrochemically tested in the same way as in Example 1. The test results are shown in Table 1.

[0053] Example 6

[0054] The only difference between Example 6 and Example 1 is that the thickness of the nitrogen-fluorine co-doped three-dimensional carbon material layer formed on the aluminum foil is 50 μm. The rest is the same as in Example 1. The nitrogen-fluorine co-doped three-dimensional carbon material was prepared and a sodium-ion battery was assembled and electrochemically tested using the same method as in Example 1. The test results are shown in Table 1.

[0055] Example 7

[0056] The only difference between Example 7 and Example 1 is that the homogeneous mixture was placed in a tube furnace and heated to 600°C. The rest of the process was the same as in Example 1. Nitrogen-fluorine co-doped three-dimensional carbon material was prepared and assembled into a sodium-ion battery using the same method as in Example 1. Electrochemical tests were then performed, and the test results are shown in Table 1.

[0057] Example 8

[0058] The only difference between Example 8 and Example 1 is that the homogeneous mixture was placed in a tube furnace and heated to 1000°C. The rest of the process was the same as in Example 1. Nitrogen-fluorine co-doped three-dimensional carbon material was prepared and assembled into a sodium-ion battery using the same method as in Example 1. Electrochemical tests were then performed, and the test results are shown in Table 1.

[0059] Example 9

[0060] The only difference between Example 9 and Example 1 is that the homogeneous mixture was placed in a tube furnace and heated to 400°C. The rest of the process was the same as in Example 1. Nitrogen-fluorine co-doped three-dimensional carbon material was prepared and assembled into a sodium-ion battery using the same method as in Example 1. Electrochemical tests were then performed, and the test results are shown in Table 1.

[0061] Example 10

[0062] The only difference between Example 10 and Example 1 is that the nitrogen source is replaced by ammonia instead of ammonium fluoride, the fluorine source is replaced by polyvinylidene fluoride instead of ammonium fluoride, sucrose and polyvinylidene fluoride are mixed in a 1:1 mass ratio to form a homogeneous mixture, and the atmosphere gas of the tube furnace is replaced by ammonia instead of argon. The rest is the same as in Example 1. A nitrogen-fluorine co-doped three-dimensional carbon material was prepared, and a sodium-ion battery was assembled using the same method as in Example 1 and electrochemical tests were performed. The test results are shown in Table 1.

[0063] Example 11

[0064] The only difference between Example 11 and Example 1 is that the nitrogen source is replaced by melamine instead of ammonium fluoride, and the fluorine source is replaced by polyvinylidene fluoride instead of ammonium fluoride. Sucrose, melamine and polyvinylidene fluoride are mixed in a mass ratio of 1:1:1 to form a homogeneous mixture. The rest is the same as in Example 1. A nitrogen-fluorine co-doped three-dimensional carbon material is prepared and a sodium-ion battery is assembled using the same method as in Example 1. Electrochemical tests are performed, and the test results are shown in Table 1.

[0065] Example 12

[0066] The only difference between Example 12 and Example 1 is that the nitrogen source is replaced by nitrogen gas instead of ammonium fluoride, the fluorine source is replaced by carbon tetrafluoride instead of ammonium fluoride, sucrose is placed separately in a tube furnace, and the atmosphere gas in the tube furnace is replaced by a 1:1 mixture of ammonia and carbon tetrafluoride instead of argon. The rest is the same as in Example 1. A nitrogen-fluorine co-doped three-dimensional carbon material was prepared, and a sodium-ion battery was assembled using the same method as in Example 1. Electrochemical tests were performed, and the test results are shown in Table 1.

[0067] Example 13

[0068] The only difference between Example 13 and Example 1 is that sucrose is replaced with glucose. The rest is the same as in Example 1. Nitrogen-fluorine co-doped three-dimensional carbon material was prepared and a sodium-ion battery was assembled using the same method as in Example 1. Electrochemical tests were performed and the test results are shown in Table 1.

[0069] Comparative Example 1

[0070] The only difference between Comparative Example 1 and Example 1 is that ammonium fluoride is not added during the preparation of the three-dimensional carbon material, resulting in a three-dimensional carbon material without nitrogen and fluorine doping. Then, the negative electrode sheet is prepared, the sodium-ion battery is assembled, and electrochemical tests are performed using the same method as in Example 1. The test results are shown in Table 1.

[0071] Comparative Example 2

[0072] Comparative Example 2 used pure aluminum foil current collectors and NaNiFeMn cathodes to assemble sodium-ion batteries, and performed electrochemical tests using the same method as in Example 1. The test results are shown in Table 1.

[0073] Comparative Example 3

[0074] The only difference between Comparative Example 3 and Example 1 is that sucrose and ammonium fluoride were mixed at a mass ratio of 20:1 to form a homogeneous mixture. The rest of the process was the same as in Example 1. Sodium-ion batteries were assembled and electrochemical tests were performed using the same method as in Example 1. The test results are shown in Table 1.

[0075] Comparative Example 4

[0076] The only difference between Comparative Example 4 and Example 1 is that sucrose and ammonium fluoride were mixed in a mass ratio of 1:5 to form a homogeneous mixture. The rest of the process was the same as in Example 1. Sodium-ion batteries were assembled and electrochemical tests were performed using the same method as in Example 1. The test results are shown in Table 1.

[0077] Comparative Example 5

[0078] The only difference between Comparative Example 5 and Example 1 is that the thickness of the nitrogen-fluorine co-doped three-dimensional carbon material layer formed on the aluminum foil is 1 μm. The rest is the same as in Example 1. The sodium-ion battery was assembled and electrochemically tested in the same way as in Example 1. The test results are shown in Table 1.

[0079] Comparative Example 6

[0080] The only difference between Comparative Example 6 and Example 1 is that the thickness of the nitrogen-fluorine co-doped three-dimensional carbon material layer formed on the aluminum foil is 100 μm. The rest is the same as Example 1. The sodium-ion battery was assembled and electrochemically tested in the same way as in Example 1. The test results are shown in Table 1.

[0081] Comparative Example 7

[0082] The only difference between Comparative Example 7 and Example 1 is that the homogeneous mixture was placed in a tube furnace and heated to 300°C. The rest of the process was the same as in Example 1. Sodium-ion batteries were assembled and electrochemical tests were performed using the same method as in Example 1. The test results are shown in Table 1.

[0083] Comparative Example 8

[0084] The only difference between Comparative Example 8 and Example 1 is that the homogeneous mixture was placed in a tube furnace and heated to 1200°C. The rest of the process was the same as in Example 1. Sodium-ion batteries were assembled and electrochemical tests were performed using the same method as in Example 1. The test results are shown in Table 1.

[0085] Comparative Example 9

[0086] The only difference between Comparative Example 9 and Example 11 is that only the nitrogen source melamine was added and no fluorine source was added. The ratio of sucrose to melamine was 1:1. The rest was carried out in the same manner as in Example 11. The sodium-ion battery was assembled and electrochemically tested in the same way as in Example 11. The test results are shown in Table 1.

[0087] Comparative Example 10

[0088] The only difference between Comparative Example 10 and Example 11 is that only the fluorine source polyvinylidene fluoride was added instead of the nitrogen source, and the ratio of sucrose to polyvinylidene fluoride was 1:1. The rest was carried out in the same manner as in Example 11, and the sodium-ion battery was assembled and electrochemically tested in the same way as in Example 11. The test results are shown in Table 1.

[0089] Comparative Example 11

[0090] The preparation method of the three-dimensional carbon material in this comparative example is as follows:

[0091] (1) Dissolve 0.803 g of cetylammonium bromide (CTAB) in 240 mL of 1 mol / L solution at 0–3 °C. -1 In an HCl solution, after complete dissolution and foaming, 0.235 g of polyvinylidene fluoride (PVDF) was added and completely dispersed under magnetic stirring at 800 r / min. Then, 1.2 g of ammonium persulfate (NH4)2S2O8 was poured into the solution under stirring. Next, 1.6 mL of pyrrole monomer was slowly added dropwise to the white suspension, and polymerization was carried out under magnetic stirring for 3 h. The reactants were filtered, and the resulting product was a black powder, which was a mixture of polypyrrole fiber (PPy) and polyvinylidene fluoride (PVDF) microspheres. After washing three times each with deionized water and anhydrous ethanol, the product was dried in an 80℃ drying oven for 10 hours to obtain the precursor.

[0092] (2) At room temperature, the precursor was placed in a tube furnace and calcined at 650°C for 2 hours under a high-purity argon atmosphere at a heating rate of 5°C / min to obtain a black product, which is nitrogen-fluorine co-doped carbon nanotube.

[0093] Sodium-ion batteries were assembled using the nitrogen-fluorine co-doped carbon nanotubes and electrochemical tests were conducted. The test results are shown in Table 1.

[0094] Table 1. Electrochemical performance of sodium-ion batteries in Examples 1-12 and Comparative Examples 1-10

[0095]

[0096] Referring to Table 1, a comparison of Example 1 and Comparative Examples 1 and 2 shows that the sodium-ion battery assembled with a negative electrode current collector loaded with nitrogen-fluorine co-doped three-dimensional carbon material has a better cycle life, and Figure 1 The cycle capacity retention curves shown also corroborate this conclusion. Furthermore, comparing Example 1 with Comparative Examples 3-8, as shown in Table 1, the cell performance of Example 1 is significantly better than the comparative examples, indicating that the mass ratio of carbon, fluorine, and nitrogen sources, the thickness of the three-dimensional carbon material layer, and the heating temperature during the preparation process have a significant impact on the negative electrode. When the mass ratio of sucrose to ammonium fluoride is 1:1 and the heating temperature is 800℃, the battery with a nitrogen-fluorine co-doped three-dimensional carbon material thickness of 15 μm has the highest cycle life, indicating that the nitrogen-fluorine co-doped three-dimensional carbon material prepared under these process conditions has superior performance.

[0097] Comparing Example 11 with Comparative Examples 9 and 10, it can be seen that the sodium-ion battery assembled from nitrogen and fluorine co-doped three-dimensional carbon materials exhibits better cycle life compared to single-doped carbon materials. This is because the simultaneous doping of nitrogen and fluorine elements can shorten the band gap of carbon, significantly improve the conductivity of the carbon framework, enhance the adsorption of sodium ions by the framework, and reduce the diffusion energy of sodium ions in the framework, thereby reducing polarization and achieving uniform sodium deposition, thus exhibiting good synergistic effect.

[0098] In summary, the nitrogen-fluorine co-doped three-dimensional carbon material prepared by this invention possesses a high specific surface area and a porous structure. When loaded onto the negative electrode current collector of a negative electrodeless sodium-ion battery, it can effectively reduce the current density on the electrode and suppress the volume change of sodium during deposition / stripping. Furthermore, the nitrogen-containing and fluorine-containing functional groups contained in this material exhibit good sodium affinity, providing more uniform nucleation sites and a smaller nucleation overpotential for sodium deposition. It is worth mentioning that the preparation process of the nitrogen-fluorine co-doped three-dimensional carbon material is quite simple, requiring only one step, which greatly reduces the process flow, saves manufacturing costs, and has promising prospects for industrial production.

[0099] All aspects, embodiments, features, and examples of this invention are to be regarded as illustrative in all respects and are not intended to limit the invention, the scope of which is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.

[0100] In addition, the inventors of this case also conducted experiments with other raw materials, process operations, and process conditions described in this specification, referring to the aforementioned embodiments, and obtained relatively ideal results in all cases.

[0101] Although the invention has been described with reference to illustrative embodiments, those skilled in the art will understand that various other changes, omissions, and / or additions can be made without departing from the spirit and scope of the invention, and that elements of the embodiments can be substituted with substantially equivalents. Furthermore, many modifications can be made without departing from the scope of the invention to adapt particular situations or materials to the teachings of the invention. Therefore, this invention is not intended to be limited to the specific embodiments disclosed for carrying out the invention, but rather is intended to encompass all embodiments falling within the scope of the appended claims. Moreover, unless specifically stated otherwise, any use of the terms first, second, etc., does not indicate any order or importance, but is used to distinguish one element from another.

Claims

1. A method for preparing a nitrogen-fluorine co-doped three-dimensional carbon material, characterized in that, include: Under a protective atmosphere, a homogeneous mixture containing an organic carbon source, a fluorine source, and a nitrogen source is heated at 400–1000 °C to obtain a nitrogen-fluorine co-doped three-dimensional carbon material.

2. The preparation method according to claim 1, characterized in that: The organic carbon source includes sucrose and / or glucose; And / or, the nitrogen source includes at least one of ammonium fluoride, melamine, ammonia and nitrogen; And / or, the fluorine source includes at least one of ammonium fluoride, polyvinylidene fluoride, and carbon tetrafluoride; And / or, the mass ratio of the organic carbon source, nitrogen source, and fluorine source is 1:(0.1-2):(0.1-2); And / or, the heating time is 1h to 6h.

3. The preparation method according to claim 2, characterized in that: The homogeneous mixture comprises sucrose and ammonium fluoride in a mass ratio of 1:2 to 10:

1.

4. The nitrogen-fluorine co-doped three-dimensional carbon material obtained by the preparation method according to claims 1 to 3; Preferably, the nitrogen doping amount in the nitrogen-fluorine co-doped three-dimensional carbon material is 0.01% to 1%, and the fluorine doping amount is 0.01% to 1%. Preferably, the specific surface area of ​​the nitrogen-fluorine co-doped three-dimensional carbon material is 80 m². 2 / g~500m 2 / g; Preferably, the porosity of the nitrogen-fluorine co-doped three-dimensional carbon material is 25% to 75%.

5. A slurry composition, characterized in that: The slurry composition comprises the nitrogen-fluorine co-doped three-dimensional carbon material as described in claim 4.

6. The slurry composition according to claim 5, characterized in that, The slurry composition further includes a dispersant, a conductive agent, and a binder; Preferably, the dispersant comprises water and / or N-methylpyrrolidone, more preferably N-methylpyrrolidone; and / or, the conductive agent comprises at least one of conductive carbon black, carbon nanotubes and graphene; and / or, the binder comprises at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid and polyvinylidene fluoride.

7. The slurry composition according to claim 6, characterized in that: The nitrogen-fluorine co-doped three-dimensional carbon material has a content of 30% to 70% in the slurry composition.

8. The application of the nitrogen-fluorine co-doped three-dimensional carbon material of claim 4 or the slurry composition of any one of claims 5 to 7 in the preparation of a negative electrode for a secondary battery or a secondary battery.

9. A negative electrode for a sodium-ion battery, characterized in that, It includes the nitrogen-fluorine co-doped three-dimensional carbon material as described in claim 4.

10. A sodium-ion battery without negative electrode active material, comprising a positive electrode, a negative electrode, and an electrolyte, characterized in that: The negative electrode includes a current collector and a carbon material layer disposed on the current collector, wherein the carbon material layer comprises the nitrogen-fluorine co-doped three-dimensional carbon material as described in claim 4.

11. The sodium-ion battery without negative electrode active material according to claim 10, characterized in that: The thickness of the carbon material layer is 2–50 μm.

Citation Information

Cited By

  • Fluorine-containing porous carbon, negative electrode material and preparation method thereof

    CN122187012A